2020
DOI: 10.1152/ajpheart.00569.2019
|View full text |Cite
|
Sign up to set email alerts
|

Lactobacillus reuteri attenuates cardiac injury without lowering cholesterol in low-density lipoprotein receptor-deficient mice fed standard chow

Abstract: We demonstrated that daily delivery of Lactobacillus reuteri to wild-type and hypercholesterolemic lipoprotein receptor knockout mice attenuated cardiac injury following ischemia-reperfusion without lowering total serum cholesterol in the short term. In addition, we validated protection against cardiac injury using histology and immunohistochemistry techniques. L. reuteri offers promise as a probiotic to mitigate ischemic cardiac injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 54 publications
0
8
0
Order By: Relevance
“…Previous studies have reported the anti‐inflammatory effects of L. reuteri [ 18 ] and found the gavage of this bacteria reduced cardiac injury in low‐density lipoprotein receptor (LDLR)‐deficient mice [ 19 ] we set out to explore the cardioprotective potential of L. reuteri in the context of I/R ( Figure 1 A ). Male C57BL/6J were given oral antibiotics for seven days to deplete the original gut microbiota to facilitate the colonization of L. reuteri (copies of bacterial 16S, p < 0.001, Figure 1B ) and daily gavage of L. reuteri as a prophylactic (2 × 10 8 CFU per mouse) or PBS (control) was carried out daily for 7 days.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have reported the anti‐inflammatory effects of L. reuteri [ 18 ] and found the gavage of this bacteria reduced cardiac injury in low‐density lipoprotein receptor (LDLR)‐deficient mice [ 19 ] we set out to explore the cardioprotective potential of L. reuteri in the context of I/R ( Figure 1 A ). Male C57BL/6J were given oral antibiotics for seven days to deplete the original gut microbiota to facilitate the colonization of L. reuteri (copies of bacterial 16S, p < 0.001, Figure 1B ) and daily gavage of L. reuteri as a prophylactic (2 × 10 8 CFU per mouse) or PBS (control) was carried out daily for 7 days.…”
Section: Resultsmentioning
confidence: 99%
“…IL-1β is regulated by the NF-κB, c-Jun N-terminal kinase (JNK), and p38 MAPK pathways [ 29 ]. IL-6 can be released by myocardial and immune cells [ 30 ], and is primarily triggered and regulated by signaling pathways such as NF-κB and MAPK [ 31 ]. It is reported that total glucosides of V. officinalis attenuate chronic nonbacterial prostatitis in rat models by reducing the release of IL-2, IL-1β, and TNF-α in the prostate [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…. IL-6 can be released by myocardial and immune cell [39] , mainly triggered and regulated by signalling pathways like NF-κB and MAPK [40] . It is reported that total glucosides of V. officinalis attenuate chronic nonbacterial prostatitis in rat model by reducing the release of IL-2, IL-1β and TNF-α in prostate [41] .…”
Section: Discussionmentioning
confidence: 99%